Re-reduction of CCD astrometric observations of Neptunian satellites in 2006–2007 based on Gaia DR2 and comparison with ephemerides. (January 2019) - Yu, Y.; Cheng, X.; Qiao, R.C.; Yan, D.; Luo, H.; Tang, K.
Abstract: Based on the newly released Gaia DR2 star catalogue, the CCD images of Neptunian satellites taken by the telescopes at Xinglong Observatory of National Astronomical Observatory in 2006–2007 were re-reduced. A total of 174 satellite positions were derived, including 34 new observed positions of Triton, 28 new and 112 updated observed positions of Nereid. Thanks to the high-quality reference catalogue Gaia DR2 and more suitable plate models, the precision of the re-reduction for Nereid is more than doubled and the dispersions of these observations are better than 80 mas. Moreover, the comparisons show that for the Neptune system in the period 2006–2007, there are some systematic discrepancies between different planetary ephemerides such as INPOP17a with DE431 and EPM2017, and the discrepancy can reach as much as 50 mas, which is reflected in the calculation of (OC) residuals of Neptunian satellites. Highlights: It is necessary to improve the precisions of old observations for natural satellites. The old observations of Neptunian satellites in 2006-2007 were reduced based on Gaia DR2 catalogue. 34 new observed positions of Triton, 28 new and 112 updated observed positions of Nereid were presented. The precision of the re-reduction for Nereid is better than 80 mas.